Parameter Entomologi pada Daerah Endemis Demam Berdarah Dengue Tinggi dan Rendah di Jawa Tengah (Studi di Kabupaten Kudus dan Wonosobo) - Bina Ikawati; Bondan Fajar Wahyudi; Novia Tri Astuti; Sunaryo Sunaryo (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Kudus district is a district with high DHF cases in Central Java in 2013 (IR=57.50). Wonosobo District is new area with low DHF cases (IR=11.92). Aedes aegypti is the main vector of DHF in both. The purpose of this study was to determine the difference of entomological parameter in high and low DHF endemic area. This research was continued analysis of entomologycal data from study of The Resistance Map of Aedes aegypti (Linn) Agains Cypermethrin 0,05%, Malathion 0,8% and Temephos inn Purworejo, Kebumen, Pekalongan, Demak, Wonosobo, Cilacap, Kudus, Klaten, Banjarnegara at 2014, that use cross sectional design. The results showed that HI, CI, BI and PI in Kudus (40,67%,21,40%, 233,67 and 113,67%), higher than in Wonosobo (14,33%, 10,93%, 15,33 dan 38,33%). In all location bathing tub were the potential breeding places of Ae. aegypti. In Kudus, Breeding Preference Ratio (BPR) in barrel and water tank for “wudhu” had the highest as much as 4.03. In Wonosobo the highest BPR was in jar as much as 9.15. Multivariat analysis showed that in Kudus container covers were most closely correlated to the presence of Ae. aegypti larvae, while in Wonosobo illumination around containers is the main factor.